2020
DOI: 10.1021/acs.nanolett.9b05218
|View full text |Cite
|
Sign up to set email alerts
|

Treating Acute Kidney Injury with Antioxidative Black Phosphorus Nanosheets

Abstract: Black phosphorus nanosheets (BPNSs) have been actively employed as nanomedicine agents for photothermal and photodynamic therapy by virtue of their unique optical properties. However, their chemical reactivity as a competent biomaterial has not been fully explored yet. Here, we report on the use of BPNSs as reactive oxygen species (ROS) scavengers to cure acute kidney injury (AKI) in mice. Importantly, in vivo analysis in mice revealed that BPNSs were preferably accumulated in kidney. We found that BPNSs allev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(144 citation statements)
references
References 38 publications
2
131
0
11
Order By: Relevance
“…The properties of biocompatibility and biodegradability of BPNSs were also outstanding, increasing the chances of further development of novel nanomaterials for application in AKI treatments. [130] fibrosis [60,61]. Nanotechnology-based drug delivery systems give insight to AKI therapies but remain challenging on account of the glomerular filtration barrier (GFB) [10,62].…”
Section: Ros-targeted Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of biocompatibility and biodegradability of BPNSs were also outstanding, increasing the chances of further development of novel nanomaterials for application in AKI treatments. [130] fibrosis [60,61]. Nanotechnology-based drug delivery systems give insight to AKI therapies but remain challenging on account of the glomerular filtration barrier (GFB) [10,62].…”
Section: Ros-targeted Therapymentioning
confidence: 99%
“…Recent studies have shown the powerful effects of the BPNSs in the targeted cancer phototheranostics and neurodegenerative disorder therapy, which mostly rely on their physical properties, such as shape, size, and optical properties [129]. Besides their excellent physical characteristics, BPNSs also exhibit chemical reactivity toward ROS [130]. The layer-packed structure of BPNSs promotes the electron transfer as well as the oxidative reaction, leading to the excellent capability of scavenging ROS [131].…”
Section: Black Phosphorus Nanosheetsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Additionally, metal-free nanoagents such as DNA origami nanostructures and black phosphorus nanosheets have been used to alleviate AKI. 7,12 However, translation of these nanoagents faces several potential roadblocks including ambiguous in vivo stability, indenite immune responses, and potential acute toxicity. 13,14 As of now, the engineering of antioxidative nanoagents for treating renal diseases is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Small molecular antioxidants, such as N-acetyl cysteine (NAC), can be utilized as an alternative to protect against chemotherapy-induced AKI by reducing oxidative damage 9 . Recently, nanomaterials with ROSregulating capacities have been studied to broaden the therapeutic strategies for ROS-involved diseases, including AKI [10][11][12][13] . For example, molybdenum-based polyoxometalate nanoclusters were fabricated as nano-antioxidants that preferentially accumulated in kidneys for efficient renal protection 14 ; DNA origami nanostructures had demonstrated a potent ROS scavenging capacity to protect kidney structures and ameliorate AKI 15 .…”
mentioning
confidence: 99%